Penerapan Metode Resource Based Learning Dalam Meningkatkan Kreativitas Dan Hasil Belajar Ipa Terpadu SMP Swasta Nupela Tahun Pembelajaran 2023/2024 - Tiurwati Telaumbanua (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2023)
This study aims to describe and prove a significant improvement in the quality of learning, student creativity, and learning outcomes in Integrated Science subjects through the application of the Resource Based Learning (RBL) method at NUPELA Private Junior High School. This study is a Classroom Action Research (CAR) conducted in two cycles. The research subjects consisted of 25 students of class VIII-A in the 2023/2024 academic year. Data collection was carried out using observation sheets, learning outcome tests, learning quality and creativity questionnaires, and interviews. Quantitative data analysis used the Z test and t test at a significance level of 5%. The results showed a significant increase in all measured indicators. The quality of learning increased from an average of 67.35% in Cycle I to 93.4% in Cycle II, which was proven significantly through the Z test (Z_count = 2.13 > Z_table = 1.64). Student creativity also increased from 67.60% to 92.90% and was proven significant (Z_count = 2.08 > Z_table = 1.64). The average learning outcomes increased from 69.18 (60% completion) in Cycle I to 81.54 (84% completion) in Cycle II, which was also proven significant based on the t-test (t_count = 4.684 > t_table = 1.711). The implications of this study indicate that the direct use of various learning resources through the RBL method is effective in triggering student activity, creating a pleasant learning atmosphere, and significantly improving student creativity and academic performance.